Plasma haptoglobin level can augment NT-proBNP to predict poor outcome in patients with severe acute decompensated heart failure. (3rd October 2018) - Lu, Dai-Yin; Lin, Chih-Pei; Wu, Cheng-Hsueh; Cheng, Tsai-Mu; Pan, Ju-Pin
Abstract : To evaluate the use of plasma haptoglobin (Hp) levels and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in predicting survival in patients with severe acute decompensated heart failure (AHF). Management of AHF is challenging. Identifying markers associated with patient prognosis in this disease is clinically important. In this prospective observational study, plasma Hp and NT-proBNP levels were measured. Receiver operating characteristic (ROC) curves were used to identify cut-offs of Hp and NT-proBNP with the greatest specificity and sensitivity for predicting overall survival and cardiovascular-related survival. The cut-off values were tested in patients with AHF (n=41). The cut-off value with the greatest specificity and sensitivity with respect to overall survival and for cardiovascular-related survival for Hp was 177. 1 ng/mL for both outcomes and for NT-proBNP was 34 246.0 pg/mL and 11 848.5 ng/mL, respectively. Using these cut-off values, this study found that patients with lower baseline Hp levels (<177. 1 ng/mL) or higher baseline NT-proBNP (≥34 246 pg/mL) were more likely to have shorter overall survival. Similarly, patients with <177. 1 ng/mL of Hp and ≥11 848.5 pg/mL of NT-proBNP had the highest risk of death related to cardiovascular disease. Our findings indicate that Hp and NT-proBNP using specific cut-off values for AHF can be used to determine risk of survival in these patients.